Perceived organizational support and organizational commitment in medium enterprises in Malaysia - Wahab, Eta (Curtin University, 2010)
This research focuses on the antecedents of perceived organizational support (POS) that may influence the perceptions held by employees of medium enterprises on organizational commitment. This research further investigates the relationship between POS and organizational commitment. The effect of power distance and in-group collectivism culture on organizational commitment in the context of the Malaysian cultural perspective has also been examined along with the effect of value congruence on organizational commitment.A two-phase sequential mixed method research design consisting of qualitative and quantitative approaches has been employed in this research. A tentative research model was first developed based on an extensive literature review followed by qualitative field study. Findings from the qualitative study were then combined with the initial model and literature review to develop the final combined model, which was then used to develop measures and instruments.In the second phase, a survey was conducted of 1000 employees in Malaysian medium enterprises in the manufacturing sector. 319 valid questionnaires were obtained. Partial Least Squares (PLS) based Structural Equation Modeling (SEM) approach was applied to test the hypotheses.The result of this research showed that supervisor support, procedural justice, interactional justice, distributive justice and both intrinsically and extrinsically satisfying job conditions have positive influences on employees‟ perception of support. POS was found to have a significant role contributing towards affective commitment. However, the influence of POS on both normative and continuance commitment was found to be non-significant in this study.This study also confirmed the influence of POS on value congruence. Both affective and normative commitment, were found to be non-significant in relation to POS. In contrast, employee–organization value congruence was found to influence continuance commitment. The analysis also found that external factors do not limit continuance commitment. National culture was found to have a different impact towards organizational commitment. The findings also revealed that the strength of the relation between POS and employees‟ commitment is negatively moderated by in-group collectivism, however power distance was found to moderate the influence of POS only on normative commitment.This research contributes to the existing literature as there has been little evidence found in the literature relating to the GLOBE culture dimensions with organizational commitment, especially in medium enterprises. This study also extends culture literature by showing that culture can act as a moderator of the relationship between POS and both affective and normative commitment. By considering value congruence, perception of support, as well as cultural orientation, this study will benefit practitioners and policy makers of medium enterprises on how to foster organizational commitment.